Pemanfaatan dan Pengembangan Obyek Arkeologi di Padang Lawas dan Padang Lawas Utara Sebagai Kawasan Wisata Budaya Terpadu - Repelita Wahyu Oetomo (Balai Arkeologi Sumatera Utara, 2011)
AbstractPadang Lawas area has many archaeological remains. This potential will be very interesting if the utilization anddevelopment as a tourism destination combined with other natural resources, such as natural conditions, flora, and fauna.